2012
DOI: 10.1111/j.1365-2354.2012.01369.x
|View full text |Cite
|
Sign up to set email alerts
|

The utility of the Edmonton Symptom Assessment System in screening for anxiety and depression

Abstract: The Edmonton Symptom Assessment System (ESAS) is a common screening tool in cancer, although its validity for distress screening is unproven. Here, screening performance of the ESAS anxiety (ESAS-A) and depression (ESAS-D) items were validated against the anxiety [Generalised Anxiety Disorder-7 (GAD-7)] and depression [Patient Health Questionnaire-9 (PHQ-9)] subscales of the PHQ. A total of 1215 cancer patients completed the Distress Assessment and Response Tool (DART), a computerised distress screening instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 59 publications
3
50
1
Order By: Relevance
“…These studies did not assess the diagnostic accuracy of PROMIS ® CAT in comparison to legacy measures using a Receiver Operator Characteristic (ROC) methodology. The use of ROC has been previously used to test the discriminant power for comparison of outcome measures as expressed in sensitivity and specificity in the osteoporosis and cancer populations and to determine important cutoff scores for use in clinical practice [40][41][42] . Whereas, there have been some cross-walking of the FACIT-Fatigue scores to PROMIS ® T-scores 43 , comparison of legacy measures for insomnia and PROMIS has not been previously examined.…”
Section: Accepted Articlementioning
confidence: 99%
“…These studies did not assess the diagnostic accuracy of PROMIS ® CAT in comparison to legacy measures using a Receiver Operator Characteristic (ROC) methodology. The use of ROC has been previously used to test the discriminant power for comparison of outcome measures as expressed in sensitivity and specificity in the osteoporosis and cancer populations and to determine important cutoff scores for use in clinical practice [40][41][42] . Whereas, there have been some cross-walking of the FACIT-Fatigue scores to PROMIS ® T-scores 43 , comparison of legacy measures for insomnia and PROMIS has not been previously examined.…”
Section: Accepted Articlementioning
confidence: 99%
“…Unfortunately it appears that the ESAS scores are currently not easily accessible to RTs. Since many respondents believe that including this symptom analysis is important in the RTs' daily clinical practice, and has been found in other studies to be reliable in screening for anxiety and depression [1,12], this should be an area for future study to improve the ability of RTs to easily access and use ESAS information.…”
Section: Page 13mentioning
confidence: 99%
“…This patient-reported information is typically utilized by the Radiation Oncologist and Radiation Oncology Nurses, however is not always utilized by the RTs. It has been found that ESAS is a simple but valid tool for assessing anxiety and depression in patients [1,12].…”
Section: Introductionmentioning
confidence: 99%
“…Vignaroli et al (42). They found that ESAS-Depression performed well compared to PHQ-9 sumscore (≥10 of 27) and proposed ESAS-Depression as an initial screening instrument to exclude non-depressed patients before screening with a more extended instrument.…”
Section: Esas-depression -A Valid Indicator Of Depression?mentioning
confidence: 99%
“…In a two-step screening procedure, sensitivity in the first step would be most important to not overlook depressed subjects; sensitivity of 0.85 was considered putative for this purpose (42). …”
Section: Sensitivity and Specificity Indication For Clinical Supportmentioning
confidence: 99%